2022
DOI: 10.1186/s13244-022-01273-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CT-based radiomics predicts pathological complete response after neoadjuvant chemotherapy for advanced adenocarcinoma of the esophagogastric junction: a two-center study

Abstract: Purpose This study aimed to develop and validate CT-based models to predict pathological complete response (pCR) after neoadjuvant chemotherapy (NAC) for advanced adenocarcinoma of the esophagogastric junction (AEG). Methods Pre-NAC clinical and imaging data of AEG patients who underwent surgical resection after preoperative-NAC at two centers were retrospectively collected from November 2014 to September 2020. The dataset included training (n = 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…After screening the titles and abstracts, 177 studies were selected for full-text reading. Finally, 9 studies, comprising 23 cohorts, were included for assessing the diagnostic accuracy of AI algorithms in predicting the response of GC to neoadjuvant chemotherapy (29)(30)(31)(32)(33)(34)(35)(36)(37). Out of these, 7 head-tohead studies were analyzed to compare the diagnostic accuracy of AI, CM, and IM.…”
Section: Study Selectionmentioning
confidence: 99%
“…After screening the titles and abstracts, 177 studies were selected for full-text reading. Finally, 9 studies, comprising 23 cohorts, were included for assessing the diagnostic accuracy of AI algorithms in predicting the response of GC to neoadjuvant chemotherapy (29)(30)(31)(32)(33)(34)(35)(36)(37). Out of these, 7 head-tohead studies were analyzed to compare the diagnostic accuracy of AI, CM, and IM.…”
Section: Study Selectionmentioning
confidence: 99%
“…Hosmer-Lemeshow test were used to evaluate the correction ability of the model. In the Hosmer-Lemeshow test, p > 0.05 indicated no significant difference between the predicted and real value [22]. Calibration curves and decision curves were used to evaluate the optimal model.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this is related to the decline of physical function in the elderly and the resistance to chemotherapy drugs [42]. Furthermore, the RECIST are limited due to the varying degree of gastric filling and low reproducibility of data measurements, which may bias the results [22,43]. Studies have shown that Borrmann type III and IV gastric cancers have a low survival rate and poor prognosis [44,45], while TRG after NAC was also significantly correlated with prognosis [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Recent studies have depicted that combining radiomics signatures with clinical factors indicates excellent potential in the diagnosis and prognosis of the disease. 33,34 Routine blood tests have a significant role in diagnosing diseases and observing the curative effect and prognosis and are a commonly used clinical examination method. NEU, LYM, and MONO are common infection indicators and systemic inflammation inside the body.…”
Section: Model Validation and Comparisonmentioning
confidence: 99%